The Importance of Dialogue for Pastoral Theological Development: Some Reflections on van Holten and Walton's Theological Method and its Problems with the "Timelessness of God". (28th January 2022) - Swinton, John; Brock, Brian
Abstract : In response to van Holten and Walton's critique (van Holten & Walton, 2020, 2022) of John Swinton's theological approach to time and disability (Swinton, 2016, 2020), John Swinton is joined by the theological ethicist Professor Brian Brock. Swinton and Brock argue that while van Holten and Walton claim to be attempting to open up a dialogue, this is debatable. Dialogue is necessary for conversations such as these, but the thrust of their work has been focused on criticism and argument, without any constructive proposals for theory or practice. This might be acceptable if we were simply discussing concepts and ideas. It is less convincing when we are dealing with real people. As per their previous work, van Holten and Walton constantly attempt to push their ideas into practice without actually taking experience into consideration, which leads to significant contradictions and problems. In this article, we explore van Holten and Walton's approach to theology and doing theology – what theology is, who should be allowed to participate in its formation and what approaches are considered appropriate, and, importantly, who makes that decision. We examine some of the significant problems with their position when it comes to examining complex real-world issues such as the experience of dementia and disability. The current article engages with the various criticisms and concerns that are put forward, and highlights some of our concerns and worries about the flaws in their approach and their lack of awareness of or attention to its implications for practice. Despite the fact that we are far apart on many issues, the article concludes that there may actually be a way forward if the desire for dialogue is taken seriously. The article ends with a constructive proposition that has the potential to positively ground and encourage future conversations between practical and philosophical theology.